Indoor Environment Quality (IEQ) at Menara Sarawak Energy: An Analysis on Post Occupancy Satisfaction and Working Performance of Building Occupants - Siew, Amanda Moh Tiing; Kamarazaly, Myzatul Aishah; Ling, Shirley Chin Ai; Harun, Hasmawati (MAJ - Malaysia Architectural Journal, 2023)
Post occupancy survey was important for occupants to give feedback on the IEQ for further improvement, but it was a rare practice in Malaysia. Furthermore, there was no case studies conducted to investigate the IEQ issues present in Menara Sarawak Energy (MSE). Therefore, this research aimed to study the effects of IEQ towards building occupants’ working performance in MSE. The objectives of this research were to identify factors influencing the IEQ in MSE, to investigate the building occupants’ satisfaction level on the IEQ, to investigate the effects of IEQ towards the building occupants’ working performance, and to propose appropriate solutions for the improvement of IEQ to ensure better working performance. Both qualitative and quantitative methods were carried out. Interviews had been conducted with three (3) Building, Facility and Infrastructure (BFI) key leaders to collect data regarding the possible IEQ issues in MSE while 254 valid survey responses were collected to investigate the occupants’ satisfaction level on the IEQ and the effects of IEQ on their working performance. Thus, the findings encouraged the construction industry to use findings of this research study to improve the quality of design standards of future office projects to have a healthier working environment.